SPL7 and SPL8 represent a novel flowering regulation mechanism in switchgrass. Issue 3 (5th March 2019) - Gou, Jiqing; Tang, Chaorong; Chen, Naichong; Wang, Hui; Debnath, Smriti; Sun, Liang; Flanagan, Amy; Tang, Yuhong; Jiang, Qingzhen; Allen, Randy D.; Wang, Zeng‐Yu
Summary: The aging pathway in flowering regulation is controlled mainly by microRNA156 (miR156). Studies in Arabidopsis thaliana reveal that nine miR156‐targeted SQUAMOSA PROMOTER BINDING‐LIKE (SPL) genes are involved in the control of flowering. However, the roles of SPL s in flowering remain elusive in grasses. Inflorescence development in switchgrass was characterized using scanning electron microscopy (SEM). Microarray, quantitative reverse transcription polymerase chain reaction (qRT‐PCR), chromatin immunoprecipitation (ChIP)‐PCR and EMSA were used to identify regulators of phase transition and flowering. Gene function was characterized by downregulation and overexpression of the target genes. Overexpression of SPL7 and SPL8 promotes flowering, whereas downregulation of individual genes moderately delays flowering. Simultaneous downregulation of SPL7 / SPL8 results in extremely delayed or nonflowering plants. Furthermore, downregulation of both genes leads to a vegetative‐to‐reproductive reversion in the inflorescence, a phenomenon that has not been reported in any other grasses. Detailed analyses demonstrate that SPL7 and SPL8 induce phase transition and flowering in grasses by directly upregulating SEPALLATA3 ( SEP3 ) and MADS32 . Thus, the SPL7 / 8 pathway represents a novel regulatory mechanism in grasses that is largely different from that in Arabidopsis . Additionally, genetic modification of SPL7 and SPL8 results in much taller plants with significantly increased biomass yield and sugar release.